2009
DOI: 10.1021/jp8113013
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte Counteracts Urea-Induced Denaturation of α-Chymotrypsin

Abstract: The stability of proteins is reduced by urea, which is methylamine and nonprotecting osmolyte; eventually urea destabilizes the activity and function and alters the structure of proteins, whereas the stability of proteins is raised by the osmolytes, which are not interfering with the functional activity of proteins. The deleterious effect of urea on proteins has been counteracted by methylamines (osmolytes), such as trimethylamine N-oxide (TMAO), betaine, and sarcosine. To distinctly enunciate the comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 64 publications
11
134
1
1
Order By: Relevance
“…Indeed, TMAO acts as a strongest stabilizer for various biomolecules. [13][14][15][16][17][18]26,60 However, in the present study TMAO proved to be a weakest stabilizer. Analogously, a similar phenomenon was observed by Bruździak et al 73 According to Bruździak et al, TMAO has acted as a weak stabilizer for hen egg white lysozyme.…”
Section: Molecular Dynamics (Md) Simulationcontrasting
confidence: 59%
See 1 more Smart Citation
“…Indeed, TMAO acts as a strongest stabilizer for various biomolecules. [13][14][15][16][17][18]26,60 However, in the present study TMAO proved to be a weakest stabilizer. Analogously, a similar phenomenon was observed by Bruździak et al 73 According to Bruździak et al, TMAO has acted as a weak stabilizer for hen egg white lysozyme.…”
Section: Molecular Dynamics (Md) Simulationcontrasting
confidence: 59%
“…The native structure of proteins is only marginally stable, and achieves stability/destability only within narrow ranges of conditions of co-solvent environment which can dramatically affect the protein functional activities. [8][9][10][11][12][13][14][15] It is well-known fact that even a marginal change in the natural environment around the protein may cause adverse effects on its properties. 13 The co-solvent is oen used by physical chemist or biochemist that either stabilizes or destabilizes the structures of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that the stabilizing effects of methylamines and denaturing effects of urea on protein stability and function are additive (14,16,17,27,(62)(63)(64). As shown by Bolen's group, the protein backbone is the key determinant for the stabilization or denaturation by osmolytes (17,22,25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cartilaginous fish concentrate trimethylamine N-oxide (TMAO), to offset the damaging effects of urea on protein function, and it is one of the best studied protecting osmolytes (e.g. 16 -20).The mechanisms by which protecting osmolytes promote protein folding, increase protein stability, and induce conformational changes have been the focus of intense investigation (15,18,19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). However, nothing is known about the effects of denaturing or protecting osmolytes on the mechanical properties of PKD domains.…”
mentioning
confidence: 99%
“…Intracellular betaine serves as an osmolyte that regulates cell volume and thereby tissue integrity (Lang 2007;Schliess and Haussinger 2002). It also serves as a "compensatory" or "counteracting" solute that stabilizes proteins and is particularly effective at countering the denaturing effect of urea (Venkatesu et al 2009). These functions of betaine have been most thoroughly studied in renal medulla, where cells are normally exposed to high extracellular osmolarity during normal operation of the urinary concentrating mechanism (Neuhofer and Beck 2005).…”
Section: Betaine and Osmoregulationmentioning
confidence: 99%